Developing a Dwarf Echinacea purpurea Line by Suppressing DWF3 Expression via RNA Interference - Zhao, Jin; Fu, Yuan-Yuan; Park, Jong-Hwa; Choi, Geun-Won; Park, Kong Young; Lee, Youn Hyung; Chung, In Sik (Weon'ye gwahag gi'sulji, 2017)
DWARF3 (DWF3) is a brassinosteroid (BR) biosynthesis-related enzyme that catalyzes theC-3 oxidation of early BR intermediates. For the first time, we isolated the EpDWF3 gene fromEchinacea purpurea . EpDWF3 shares high homology with At CYP90A1 and Ze CPD1, a steroid23-alpha-hydroxylase involved in the BR-biosynthetic pathway. We generated transgenicEchinacea plants via transformation with an RNA interference (RNAi) construct that expresseshairpin double-stranded RNA for EpDWF3 to induce sequence-specific RNA silencing. Thetransgenic plants displayed dwarf phenotypes, including reduced plant height and smallflower diameter. We confirmed the presence of the RNAi construct in the transgenic plants bygenomic DNA PCR. The transcript level of EpDWF3 decreased by 48% in the transgenic plantscompared to wild type. Our results indicate that the knock-down of BR biosynthesis-relatedgenes by RNAi enables the production of valuable dwarf plants for commercial horticultural oragricultural applications. KCI Citation Count: 0